Low power electronic interface for electrostatic energy harvesters. (November 2015) - Phan, Tra Nguyen; Azadmehr, Mehdi; Le, Cuong Phu; Halvorsen, Einar
Abstract: This paper presents design and simulation of a power electronic interface circuit for MEMS electrostatic energy harvesters. The designed circuit is applicable to highly miniaturized electrostatic harvesters with small transducer capacitances below 10 pF. It is based on comb- drive harvesters with two anti-phase capacitors that are connected as charge pumps and uses a flyback-path scheme. Controlled activation and deactivation of sub-circuits, some by help of clocking, were exploited to reduce power consumption down to 1.03 μ W. Net power generation can be achieved with as low initial voltage as 3.0 V.